2010
DOI: 10.1055/s-0030-1249358
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in Pregnancy: A Systematic Approach

Abstract: Trauma in pregnancy remains one of the major contributors to maternal and fetal morbidity and mortality. Potential complications include maternal injury or death, shock, internal hemorrhage, intrauterine fetal demise, direct fetal injury, abruptio placentae, and uterine rupture. The leading causes of obstetric trauma are motor vehicle accidents, falls, assaults, and gunshots, and ensuing injuries are classified as blunt abdominal trauma, pelvic fractures, or penetrating trauma. Many of the assessment and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
2
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 45 publications
0
77
2
15
Order By: Relevance
“… Circumstances of injury In our study, the circumstances of the injury were dominated by road traffic accident in 82.6% of cases; falls in 9.8% and assaults in 7.6% of cases. Some authors have reported a predominance of road traffic accidents with frequencies between 49% and 74.3% [2] [6] [7]. The high frequency of road traffic accidents in Traore et al and our series, respectively 74.3% and 82.6% could be related to lack of strict implementation of the road traffic regulations.…”
Section:  Frequencycontrasting
confidence: 42%
See 3 more Smart Citations
“… Circumstances of injury In our study, the circumstances of the injury were dominated by road traffic accident in 82.6% of cases; falls in 9.8% and assaults in 7.6% of cases. Some authors have reported a predominance of road traffic accidents with frequencies between 49% and 74.3% [2] [6] [7]. The high frequency of road traffic accidents in Traore et al and our series, respectively 74.3% and 82.6% could be related to lack of strict implementation of the road traffic regulations.…”
Section:  Frequencycontrasting
confidence: 42%
“…In the pelvic fractures, the risk of fetal injury is more important if the presentation is cephalic and fixed. A pelvic fracture is not a definite contraindication for vaginal delivery even in the presence of a slightly displaced pelvic fracture [2] [10]. Abdominal contusions were mostly observed during road traffic accidents involving motorcycles and during assaults.…”
Section:  Pelvic Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…Head injury is especially devastating and can increase the overall morbidity and mortality. 10 Motor vehicle accidents are the commonest cause of head injury in pregnant patients. Importantly, significant trauma is associated with higher chances of fetal mortality when compared with maternal deaths.…”
Section: Head Injurymentioning
confidence: 99%